2008
DOI: 10.1111/j.1365-2702.2007.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and morningness–eveningness of shift nurses

Abstract: Our results suggested that determining if nurses were attributed to morning or evening types is an important sleep issue before deciding the shift assignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
3
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 17 publications
4
59
3
3
Order By: Relevance
“…The questionnaire used in this study was an adaptation of the questionnaire developed by Sveinsdottir [9,16,17], supplemented with some questions of the Job Content Questionnaire (JCQ) developed by Karasek et al (1998) [12]. The original instrument proposed by Sveinsdottir was in Icelandic, so the English translations of the questions were prepared, mainly from articles published by the author.…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire used in this study was an adaptation of the questionnaire developed by Sveinsdottir [9,16,17], supplemented with some questions of the Job Content Questionnaire (JCQ) developed by Karasek et al (1998) [12]. The original instrument proposed by Sveinsdottir was in Icelandic, so the English translations of the questions were prepared, mainly from articles published by the author.…”
Section: Instrumentmentioning
confidence: 99%
“…Work-related stress can be defined as a pattern of emotional, cognitive, behavioral and physiological reactions to adverse and noxious aspects of work content, work organization and work environment [11]. One method used to assess the key features of the stress process is the Karasek Demand/ Control model [12], which focuses on the interaction between the objective demands of a job and the decision latitude of employees in meeting these demands. A study on nurses' health found that high levels of strain at work (high job demands and low job control), when compared with active work (high job demands and high job control), predicted a worse quality of life [13].…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual factors have been identified that are associated with reduced tolerance, poor sleep, and performance impairment in shift workers including age, circadian preference, and psychosocial factors (Chung et al, 2009;Folkard et al, 1978;Härmä et al, 1994;Reid and Dawson, 2001).…”
Section: Shift-work Disordermentioning
confidence: 99%
“…(Kim & Jeong, 1993;Kwon, 2005;Lee & Kim, 2003;Monk, 1994). 최근 에는 일주기수면유형이 교대근무형태나 교대근무양상보다 수 면의 질에 더 결정적 영향요인이며, 특히 저녁형이 아침형보다 수면의 질이 더 나쁘다고 보고하고 있다 (Chung, Chang, Yang, Kuo, & Hsu, 2008). 그러나 교대근무 적응력과 관련되어서는 저녁형이 아침형보다 야간근무에 더 잘 적응한다는 연구 결과 가 있다 (Hilliker, Muehlbach, Schweitzer, & Walsh, 1992 (Table 1).…”
unclassified